From the nursery - Adlam, John (Horticulture Week, 2010)
Rust Check the stems and backs of new leaves on Campanula, Fuchsia, hollyhocks, Hypericum, Iris, Mahonia. mint roses and Vinca. Spray withAmistar (SOLA 2009-0443), Bumper 250EC (SOLA 2009-0707), Systhane 20EW or Signum (SOLA 2009-1 842) on non-edible plants to reduce the damaging effects of this disease.